Programming Visual Illusions for Everyone - Bertamini, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
If you find visual illusions fascinating Programming Visual Illusions for Everyone is a book for you. It has some background, some history and some theories about visual illusions, and it describes in some detail twelve illusions. Some are about surfaces, some are about apparent size of objects, some are about colour and some involve movement. This is only one aspect of the book. The other is to show you how you can create these effects on any computer. The book includes a brief introduction to a powerful programming language called Python. No previous experience with programming is necessary. There is also an introduction to a package called PsychoPy that makes it easy to draw on a computer screen. It is perfectly ok if you have never heard the names Python or PsychoPy before. Python is a modern and easy-to-read language, and PsychoPy takes care of all the graphical aspects of drawing on a screen and also interacting with a computer. By the way, both Python and PsychoPy are absolutely free. Is this a book about illusions or about programming? It is both!
Illusions are Fun -- Programming is Fun -- PsychoPy is Fun.-Kanizsa Square -- Ponzo Illusion -- Delboeuf Illusion -- Ebbinghaus Illusion -- Münsterberg and Café Wall Illusion -- Brightness contrast and White Illusion -- Neon Colour Spreading -- Honeycomb Illusion -- Breathing Square Illusion -- Stepping Feet Illusion -- Lilac Chaser Illusion -- Hierarchical Motion Organisation -- And More: Files, Irregular Polygons and Images -- Visual Perception Glossary -- Programming Glossary.
Keywords: Engineering; Signal processing; Cognitive psychology; Arts; Computational intelligence; Technology and Engineering; Signal, Speech and Image Processing; Cognitive Psychology; Arts; Computational Intelligence